Congenital diaphragmatic hernia in association with congenital short esophagus: A case report. Issue 51 (December 2017) - Xia, Bo; Hong, Chun; Tang, Jing; Liu, Cuifen; Yu, Gang
Abstract: Rationale: Congenital diaphragmatic hernia (CDH) associated congenital anomalies are present in about 25%. Congenital short esophagus (CSE) is a relatively rare condition. Both CDH and congenital intrathoracic stomach caused by CSE can be diagnosed in utero. However, CSE can be easily misdiagnosed in utero. Patient concerns: We present a case of left CDH with CSE in a female neonate who was diagnosed at 24 weeks gestational age by antenatal ultrasound. Diagnoses: The neonate with CDH and congenital intrathoracic stomach due to CSE was confirmed by operation. Gastroesophageal reflux disease (GRED) occurred after operation. Interventions: The left diaphragm was repaired, and gastric fixation by gastropexy, gastric folding anti-reflux procedure and operation of longitudinal incision and transverse suture for pyloroplasty procedure was underwent. Gastroesophageal reflux disease (GRED) occurred after operation and jejunal tube feeding was placed. Outcomes: This patient is currently alive 12 months post-operation with GRED. Lessons: To our knowledge, this is the first documented case of this rare type of CDH combined with congenital intrathoracic stomach caused by CSE. This condition could not be surgically repaired due to the extremely short esophagus. Early recognition of intrathoracic stomach associated with CSE is important as it is associated with difficult management and significant postnatal complications. The prognosis is cautiously guarded, and the parents should be appropriately counseled.